A separating transformation in the problems of extremal decomposition of the complex plane - Bakhtin, A. K.; Dvorak, I. Y.; Denega, I. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Some extremal problems of the geometric theory of functions of complex-valued variable which are associated with estimates of functionals defined on systems of disjoint domains are studied. In particular, the main attention is paid to the investigation is the well-known Dubinin problem of extremal decomposition of the complex plane.